Strengthening teachers’ socio-emotional skills in a collaborative way at the national college of villa Alemana - Acosta Aranguiz, Lissette; Arroyo Castro, Beatriz; Catalán Cueto, Juan Pablo (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
This project is being developed at the Santa Ana campus of the National School in Villa Alemana and aims to design a proposal for improving pedagogical management to strengthen the socio-emotional competencies of secondary school teachers through collaborative and interdisciplinary work. This stems from evidence gathered through institutional assessments, SIMCE and DIA results, which reveal deficient socioemotional management among students, a lack of training tools for the teaching staff, unfamiliarity with institutional instruments, and the absence of standardized protocols. The mixed-methods approach begins with a participatory assessment, followed by the identification of theoretical frameworks, and the design of a teacher development plan.As a response, an improvement plan is proposed that includes: an evaluation of available pedagogical and human resources, systematic training for all teachers, the creation of a cross-cutting and interdisciplinary instrument, and an impact evaluation strategy. The main conceptual finding indicates that strengthening teachers’ socio-emotional skills has a positive impact on students’ holistic development, consolidating a collaborative and inclusive institutional culture. This is supported by current legislation on continuous and systematic professional development for teachers.